Evaluation of a quasi‐dimeric eugenol derivative as repellent against the stored grain insect pest Sitophilusoryzae (Coleoptera Curculionidae). Issue 6 (10th April 2022) - Abenaim, Linda; Mandoli, Alessandro; Venturi, Francesca; Bedini, Stefano; Conti, Barbara
Abstract: BACKGROUND: Essential oils (EOs) and their chemical components are often proposed as an alternative to synthetic pesticides for pest control of foodstuff insect pests. However, their low persistence and strong, spicy odour, make them poorly suitable for use to protect food. Modification of the EOs components molecules increases their molecular weight and reduce their volatility. However, the effectiveness of such modified molecules has, so far, not been tested against stored food insect pests. In this study, the intensity and the duration of the repellence against the insect pest Sitophilus oryzae of a recently synthesized quasi‐dimeric eugenol derivative (ED) (C18 H20 O4 ) were compared to those of eugenol and three eugenol related compounds. The hypothesis tested was that by its higher molecular weight and two functional groups the ED would overcome the low persistence and strong and spicy odour drawback of eugenol without compromising the repellence against insects. RESULTS: The insect behavioural tests showed a greater repellence and persistence of ED than eugenol and the three eugenol related compounds against S. oryzae . The sensory analysis of ED by panel test indicated that ED is significantly less odorous than eugenol without any spicy nor balsamic nuances in its smell profile. CONCLUSIONS: Because of its high repellence against insects and its low smell intensity for humans, ED could represent a valid repellent for the control of foodstuffs insect pests. © 2022 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : The eugenol derivative showed greater repellence and persistence against the stored grain insect pest Sitophilus oryzae than eugenol but with a less intense smell.